Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1002/hbm.20360
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial magnetic stimulation and the challenge of coil placement: A comparison of conventional and stereotaxic neuronavigational strategies

Abstract: The combination of transcranial magnetic stimulation (TMS) with functional neuroimaging has expanded the potential of TMS for human brain mapping. The precise and reliable positioning of the TMS coil is not a simple task, however. Modern frameless stereotaxic systems allow investigators to base navigation either on the subject's structural magnetic resonance imaging (MRI), functional MRI data, or the use of functional neuroimaging data from the literature, so-called ''probabilistic approach.'' The latter assum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
179
3
5

Year Published

2010
2010
2017
2017

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 265 publications
(196 citation statements)
references
References 105 publications
9
179
3
5
Order By: Relevance
“…Other important differences between our and the Hoeppner study (in press) which could explain the divergent results could be that instead the use of infrathreshold stimulation, we used suprathreshold HF-rTMS thought to increase clinical outcome (Gershon, 2003). Furthermore, the imprecise TMS-coil positioning method to target the left DLPFC (Sparing et al, 2008;Peleman et al, in press), the more heterogeneous sampling of depressed patients (not all treatment-resistant), and the concomitant pharmacological antidepressant therapy on the start of their HF-rTMS study might have biased their results (Martin et al, 2003;Herwig et al, 2007).…”
Section: Discussionmentioning
confidence: 82%
“…Other important differences between our and the Hoeppner study (in press) which could explain the divergent results could be that instead the use of infrathreshold stimulation, we used suprathreshold HF-rTMS thought to increase clinical outcome (Gershon, 2003). Furthermore, the imprecise TMS-coil positioning method to target the left DLPFC (Sparing et al, 2008;Peleman et al, in press), the more heterogeneous sampling of depressed patients (not all treatment-resistant), and the concomitant pharmacological antidepressant therapy on the start of their HF-rTMS study might have biased their results (Martin et al, 2003;Herwig et al, 2007).…”
Section: Discussionmentioning
confidence: 82%
“…The use of non-stereotaxically navigated brain areas is very common in TMS studies (Sparing et al, 2008;Beam et al, 2009). Although MRI-guided stereotaxic coil positioning is more accurate, studies have found that the International 10-20 EEG system is an acceptable and reliable method to localize brain regions, especially with large cortical areas such as the DLPFC or the VLPFC (Herwig, Satrap & Schönfeldt-Lecuona, 2003;Sparing et al, 2008;Beam et al, 2009). For instance, Herwig et al (2003) investigated the underlying anatomy of F3 and found that in the vast majority of participants the location of F3 determined with the 10-20 system was within the DLPFC.…”
Section: Discussionmentioning
confidence: 99%
“…In both groups, the coil was positioned according to the standard cranial landmarks of the International 10-20 EEG system, a common approach used in our and other laboratories (Rossi et al, 2001(Rossi et al, , 2004(Rossi et al, , 2006(Rossi et al, , 2011Sparing, Buelte, Meister, Paus & Fink, 2008;Beam, Borckardt, Reeves & George, 2009). In the DLPFC group, the stimulation was delivered by placing the wings junction of the coil on the scalp region corresponding to F3 of the international EEG 10-20 system.…”
Section: Tms Protocolmentioning
confidence: 99%
“…In both cases, stimulation for the test site was individually targeted to a region where TMS disrupted either phonological or orthographic processing, as demonstrated in an independent dataset. Importantly, functional localization of this type reduces the intersubject variance present for other (more heuristic) targeting procedures, optimizing the number of participants needed (Sparing et al, 2008;Sack et al, 2009).…”
Section: Introductionmentioning
confidence: 99%